Comparative analysis of intestinal and reproductive function in older laying hens with three egg laying levels - Qiang, Taoyan; Zhang, Keying; Zeng, Qiufeng; Ding, Xuemei; Bai, Shiping; Liu, Yan; Xu, Shengyu; Xuan, Yue; Li, Shanshan; Wang, Jianping (Frontiers in Microbiology, 2025)
IntroductionIn production, older laying hens exhibit different levels of egg production, though these hens with the same genetic background, age, and feeding conditions. It is speculated that this may be due to varying intestinal function in laying hens with different egg production levels. To verify this speculation, this experiment aims to compare the intestinal function in laying hens with different egg production levels.MethodsAfter a 6-week pre-feeding with 1,000 hens, aged 60 weeks, we observed that the overall egg-laying rate for the flock was roughly 85%. Based on the data, a total of 120 healthy Lohmann Pink laying hens, aged 66 weeks, were selected for the experiment, which established three treatment groups, low egg-laying rate (LR, 76.89% ± 1.65%), medium egg-laying rate (MR, 84.96% ± 1.01%), and high egg-laying rate (HR, 93.12% ± 1.73%).ResultsThe results indicated that the HR group exhibited significantly enhanced egg production, egg mass, feed efficiency, and qualified egg rate over the 12-week period (p < 0.05). Egg quality parameters, including Haugh units and eggshell strength, were also markedly elevated in the HR group (p < 0.05). Additionally, ovarian tissues of HR group demonstrated substantially increased activities of antioxidant enzymes, such as catalase (CAT), total antioxidant capacity (T-AOC), and glutathione (GSH) (p < 0.05). Concurrently, the mRNA expression of the antioxidant gene nuclear factor erythroid 2-related factor 2 (Nrf2) in both ovarian and reproductive tract tissues was significantly upregulated, while the expression of the pro-apoptotic gene cysteinyl aspartate 3 (Caspase 3) was downregulated (p < 0.05). Regarding intestinal health, the jejunal mucosa in the HR group displayed elevated mRNA expression of intestinal barrier-related genes, including claudin 1 (CLDN1) and mucin-2 (MUC-2) (p < 0.05). Cecal microbiota analysis further indicated that the HR group exhibited a higher relative abundance of Firmicutes (phylum), Faecalibacterium (genus), and Lactobacillus (genus) (p < 0.05), whereas the abundance of Proteobacteria (phylum) and Actinobacteriota (phylum) was significantly reduced (p < 0.01). Notably, alpha diversity indices of the cecal microbiota (observed OTUs, Shannon, Simpson, and Chao1 indices) were markedly lower in the HR group (p < 0.05). Correlation analysis highlighted a positive association between the abundance of Bacillus (genus) and egg mass.DiscussionThese results suggest that hens with higher egg-laying rates demonstrated enhanced production performance and egg quality, which may be attributed to better intestine health (better barrier function, higher enrichment of Faecalibacterium and Lactobacillus in the cecum) and reproductive system health (improved antioxidant capacity). Additionally, the SIRT1-related apoptosis pathway and Nrf2 signaling pathway were associated with the enhancement of ovarian function in this study.